Overdenture -Teeth or Implants Evaluation - P. Radina; M. Seydlová; T. Dostálová; O. Simerská; J. Zvárová (Czech Dental Chamber, 2007)
The study compares two types of prosthodontic treatment - overdentures supported own patients' teeth with ball attachments or implants. 35 patients (from 1 to 5 years recall) were evaluated. Subjectively or objectively there was found no significant difference between both groups.